Perbandingan Kemampuan Kolom Pendek Berlubang Menahan Beban Aksial Dengan Variasi Diameter Tulangan Geser - Aftoni, Mohammad; Khomari, Mohamad Galuh; Wiryasuta, I Ketut Hendra; Rifqi, Mirza Ghulam; Amin, M. Shofi'ul (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
The installation of electrical and sanitary installation pipes in reinforced concrete columns forms holes that reduce the effective cross-sectional area and decrease the column capacity. This study compares the strength of perforated columns with varying shear reinforcement diameters to columns without holes. One of the reinforcement efforts was to increase the diameter of shear reinforcement to increase the resistance to axial load. The specimens measured 120 x 120 x 450 mm, consisting of six specimens: three columns without holes and three perforated columns with variations in shear reinforcement. The experimental method was used by testing materials, concrete compressive strength, and short columns at the Banyuwangi State Polytechnic Laboratory from January to June 2025. The test results showed that the columns without holes were able to withstand an axial load of 296.71 kN, 16.79% more than the perforated columns which were only able to withstand 246.89 kN. Theoretically, the column without holes has a compressive strength of 327.501kN, 3.4% greater than the perforated column of 316.531kN. The results show that increasing the diameter of shear reinforcement does not significantly increase the axial capacity of short hollow columns. Consideration of the use of diagonal shear reinforcement as additional reinforcement in addition to increasing the diameter of shear reinforcement against axial load is a crucial aspect in the optimization of hollow column design.